Towards a personalized surgical margin for breast conserving surgery—Implications of field cancerization in local recurrence. Issue 2 (5th January 2017) - Lebya, Katarina; Garcia‐Smith, Randi; Swaminathan, Radha; Jones, Anna; Russell, John; Joste, Nancy; Bisoffi, Marco; Trujillo, Kristina
Abstract : The amount of normal tissue that should be excised during breast conserving surgery is widely debated. Tissue adjacent to breast tumors, although histologically normal, possesses many of the molecular abnormalities found in tumor tissues. Here, we propose that the ideal physical distance for a surgical margin may not be universal. Rather, an adequate surgical margin likely varies from patient to patient, depending on the biology of the tissue that remains after surgery. J. Surg. Oncol. 2017;115:109–115 . © 2017 Wiley Periodicals, Inc.